Reacting in literary studies: Crossing the threshold from quality to meaning. (July 2017) - Heinert, Jennifer; Chick, Nancy L
In this essay, the authors extend their ongoing conversations within the overarching project on "critique as signature pedagogy in the arts and humanities" by considering how the position of literary studies within this broader context may explain some of the difficulties students have with a cornerstone activity of the undergraduate literature classroom. Heinert and Chick unpack the work of literary analysis as a pedagogy that helps students develop the habits of mind of the discipline. While literary analysis has long been the signature assessment of literary studies, Heinert and Chick demonstrate how and why it can also be seen as a signature pedagogy.